History Repeats: Large Scale Synchronous Biological Turnover in Avifauna From the Plio-Pleistocene and Late Holocene of New Zealand - Rawlence, Nicolas J.; Scofield, R. Paul; McGlone, Matt S.; Knapp, Michael (Frontiers in Ecology and Evolution, 2019)
New Zealand's unique biodiversity is the product of at least 55 million years of geographic isolation, supplemented by persistent transoceanic migration. Palaeontological and genetic evidence suggest most New Zealand avifauna has colonized from Australia. We synthesize evolutionary genetic studies to show a previously unrecognized clustering of divergence times in Australian and New Zealand bird species pairs, across the avian phylogeny at the beginning of the Pleistocene, around 2.5 million years ago. The timing coincides with major climatic and vegetation changes with the initiation of the Plio-Pleistocene glacial cycles. Recent anthropogenic impacts and environmental modifications are replicating in some important ways Pleistocene glacial landscapes, resulting in a new wave of avian “native invaders” into New Zealand.